The use of Massive Open Online Course (MOOC) among vocational students - Ismail, Mohd Erfy; Hashim, Suhaizal; Ismail, Irwan Mahazir; Ismail, Affero; Razali, Nizamuddin; Mat Daud, Khairul Azhar; Khairudin, Moh. (2018)
Massive Open Online Course (MOOC) is gaining its popularity as a learning medium. This study aims to examine the potential of MOOC for Welding Technology Course, which has been designed by the researchers, in enhancing students’ literacy on MOOC-based learning, engaging the students in meaningful learning and improving their motivation to learn. The MOOC is designed based on the syllabus of vocational college (VC). The population of the study is 111 students of Welding Technology Course from VC Batu Pahat, Malaysia. A total of 32 respondents were purposively sampled and they were in the first year of their studies. Data collected using questionnaires were analyzed descriptively using Statistical Packages for Social Science (SPSS) version 20.0. The reliability of the instrument is 0.91 which shows that the dependability of the instrument is high. The findings show that the MOOC designed can increase the literacy of MOOC-based learning (3.33), motivation (3.35) and student interest (3.30), thus making the learning process more interesting in addition to improving existing teaching aids. The use of the MOOC is hoped to improve the quality of education in the vocational college.